Les produits dérivés de la firme Doyon-Rivest : publicité, multiple ou ready-made? - Lavigne, Julie (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
Since they created their Doyon-Rivest "corporate" identity in 2000, artists Mathieu Doyon and Simon Rivest have been exploring the interrelationships between advertising and art, mimicking methods of advertising in order to examine its specificities and functions. With the project Thanks for being there, Doyon/Rivest raises the interaction between advertising and art to a new level by creating promotional objects that bear their logo—objects that they then feature in a "real" advertising campaign. Doyon-Rivest is attempting to blur the border between advertising and art and to reduce, subversively, the gap between great art and a practice belonging to mass culture.